The Effect of Management Accounting Systems and Environmental Uncertainty on Managerial Performance at Pt. Agromuko Bengkulu - Siregar, Elizabeth; Ginting, Mitha Christina; Situmorang, Duma Rahel; Silalahi, Mulatua (EDUCTUM: Journal Research, 2025)
This study aims to analyze the effect of Management Accounting System (SAM) and Environmental Uncertainty on Managerial Performance at PT. Agromuko Bengkulu. In the era of industry 5.0, companies are faced with the challenges of a dynamic and unpredictable environment, such as climate change, price fluctuations, and government policies that have a direct impact on managerial decision making. The Management Accounting System is an important tool in helping managers plan, supervise, and make effective decisions. This research uses a quantitative approach with the survey method of 50 respondents consisting of managers and staff of PT Agromuko Bengkulu. The data was analyzed using the Partial Least Square-Structural Equation Modeling (PLSSEM) method through SmartPLS software. The results showed that Management Accounting System has a significant effect on Managerial Performance, as well as Environmental Uncertainty which is proven to have influence on the effectiveness and efficiency of managers' performance. These findings confirm the importance of implementing a flexible and adaptive SAM in the face of uncertainty to improve managerial performance and operational efficiency of firms.